2000
DOI: 10.1074/jbc.275.20.14799
|View full text |Cite
|
Sign up to set email alerts
|

Asp-170 Is Crucial for the Redox Properties of Vanillyl-alcohol Oxidase

Abstract: Vanillyl-alcohol oxidase is a flavoprotein containing a covalent flavin that catalyzes the oxidation of 4-(methoxymethyl)phenol to 4-hydroxybenzaldehyde. The reaction proceeds through the formation of a p-quinone methide intermediate, after which, water addition takes place. Asp-170, located near the N5-atom of the flavin, has been proposed to act as an active site base. To test this hypothesis, we have addressed the properties of D170E, D170S, D170A, and D170N variants. Spectral and fluorescence analysis, tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 44 publications
3
74
1
Order By: Relevance
“…Error-prone PCR Mutagenesis-Plasmid pBC11 contains the vao gene with a silent mutation at position 882, introducing a SalI restriction site (33). For random mutagenesis, the vao gene in pBC11 was amplified using manganese-based error-prone PCR mutagenesis (34,35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Error-prone PCR Mutagenesis-Plasmid pBC11 contains the vao gene with a silent mutation at position 882, introducing a SalI restriction site (33). For random mutagenesis, the vao gene in pBC11 was amplified using manganese-based error-prone PCR mutagenesis (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…The seven clones with the highest activity for creosol were sequenced. Wild-type VAO and its mutants were overexpressed and purified according to a previously established procedure (33,36). The enzyme purity was checked by SDS-PAGE and by size-exclusion chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…A hydrogen bond to N5 is a recurrent feature in most f lavoenzymes (42) but is absent in vannilyl-alcohol oxidase (43) and glycolate oxidase (44). Although both of these f lavoproteins exhibit a higher-than-average redox potential (45,46), the consequences of the absence of a hydrogen bond at this position are not clear.…”
Section: Characterization Of Flavin-binding Pocketmentioning
confidence: 96%
“…The side chain of this acidic residue is only 3.6 Å from flavin N5 and the reactive methylene group of the phenolic substrate (8). From studies on Asp-170 variants, we recently showed that Asp-170 is important for maintaining the high redox potential of the enzyme and thus its reactivity (11). Furthermore, these studies revealed that Asp-170 assists in covalent flavinylation, possibly by donating a proton to flavin N5 (11).…”
mentioning
confidence: 99%
“…From studies on Asp-170 variants, we recently showed that Asp-170 is important for maintaining the high redox potential of the enzyme and thus its reactivity (11). Furthermore, these studies revealed that Asp-170 assists in covalent flavinylation, possibly by donating a proton to flavin N5 (11). It has been suggested that, in the related flavocytochrome PCMH, Glu-380 fulfills a similar role during the flavinylation process (4,11,12).…”
mentioning
confidence: 99%